Medical staff morality - A. I. Litvak; V. L. Mykhaylenko; R. A. Fedorchenko (Kazimierz Wielki University, 2020)
The medical help is considered to be full when medical staff not only use medical and diagnostic technology properly, but also follow the ethical rules. The research showed questionnaire to be a good method of diagnostic for both medical staff ethical potential and the individual employee's one. The scale for assessing group ethical preferences is considered to be effective also. The data resulted in a high level of ethical values and behaviour for only every eleventh respondent include. The majority of respondents, more than two-thirds, showed an average level and one of five - showed a low ethical level, mainly due to the low ethics of males. The ethical learning is an urgent and indispensable task of the medical environment in public professional organizations. The ethical trainings for different social groups (as males, females doctors and the medical staff) should be distinctively different in content and occurred in each medical organisation annually. The medical ethics has become a professional competence factor of medical staff and it should be taken care of, both the public and administrators, heads of medical institutions at all levels of government.